Terrorism in Newsweek: Unveiling the Connection between Language, Ideology, and Power - Bambang Trisno Adi (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2016)
The study analyzes the discourse on terrorism in the Newsweek magazine and exposes how the notion of ideology and power contributes to the hegemonic representations of Muslims and Islam in the post 9/11 attacks on the World Trade Centre (WTC). Two Newsweek articles appeared on the 24th September 2001 were selected. The study employed Fairclough’s Critical Discourse Analysis (CDA); this is a five-stage analytical methodology that perceives language within a three-dimensional framework: text, discourse, and society. The representation of discourse on terrorism, as found in the analysis, supports a conception that media coverage is not merely the representation of facts but also that of ideas which has gone through various considerations incorporating the three key notions of text, discourse and society altogether. The elements within the textual level and discourse level were ideologically used to represent terrorism with regard to its actor, process, and goal, constituting a commonsense as to how it should be perceived. The study concluded that the representation of discourse on terrorism in Newsweek during the post 9/11 period was perceived from what Chomsky considers as the propagandistic approach.